2015
DOI: 10.14260/jemds/2015/1016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Effectiveness of Zinc Therapy in the Treatment of Acute Diarrhoea Among Children

Abstract: BACKGROUND: Diarrhoea is one of the leading causes of morbidity and mortality affecting children in developing countries. We studied the efficacy of zinc therapy in reducing the duration of diarrhoea. MATERIALS AND METHODS: A double-blinded randomized control study was done in 100 children between age groups 1 month to 5 years having acute diarrhoea. These children were randomly divided into 2 groups. Group 1 received oral supplementation of 20mg zinc and ORS from day one of treatment while group 2 received on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…They found increase in serum zinc level after zinc treatment in diarrhoeal children. Similar findings have been reported in other studies [14][15][16][17] . Further, Habib et al 10 showed that zinc decreases the diarrhoeal episodes with faster recovery rates in any available preparation, however better results have been seen with suspension form in terms of patients' compliance.…”
Section: Page-212supporting
confidence: 93%
“…They found increase in serum zinc level after zinc treatment in diarrhoeal children. Similar findings have been reported in other studies [14][15][16][17] . Further, Habib et al 10 showed that zinc decreases the diarrhoeal episodes with faster recovery rates in any available preparation, however better results have been seen with suspension form in terms of patients' compliance.…”
Section: Page-212supporting
confidence: 93%
“…Now the WHO and UNICEF recommended 10-14 days zinc therapy with ORS for the acute diarrhea in children. [7][8][9] Many studies had reported efficacy of Zn adjuvant therapy in children under 5 years. [7][8][9][10] However, guidelines are lacking on the use of Zn in acute diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Many studies had reported efficacy of Zn adjuvant therapy in children under 5 years. [7][8][9][10] However, guidelines are lacking on the use of Zn in acute diarrhea. The present study was planned to evaluate the effects of Zn adjuvant therapy in children in terms of improvement in stool frequency and volume and duration of diarrhea at our tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%